2016
DOI: 10.7150/ijms.16372
|View full text |Cite
|
Sign up to set email alerts
|

Overhydration Negatively Affects Quality of Life in Peritoneal Dialysis Patients: Evidence from a Prospective Observational Study

Abstract: Backgound: This study evaluated whether the hydration status affected health-related quality of life (HRQOL) during 12 months in peritoneal dialysis (PD) patients.Methods: The hydration status and the HRQOL were examined at baseline and after 12 months using a bioimpedance spectroscopy and Kidney Disease Quality of Life-Short Form, respectively in PD patients. Four hundred eighty-one patients were included and divided according to the baseline overhydration (OH) value; normohydration group (NH group, -2L≤ OH ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…O’Lone et al [ 54 ] showed that the OH/ECW ratio was an independent predictor of mortality in 529 patients undergoing PD, but the ECW/TBW ratio was not associated with increased mortality. Yoon et al [ 55 ] reported that OH was associated with lower health-related quality of life in 481 patients undergoing PD.…”
Section: Bia In Patients Undergoing Peritoneal Dialysismentioning
confidence: 99%
“…O’Lone et al [ 54 ] showed that the OH/ECW ratio was an independent predictor of mortality in 529 patients undergoing PD, but the ECW/TBW ratio was not associated with increased mortality. Yoon et al [ 55 ] reported that OH was associated with lower health-related quality of life in 481 patients undergoing PD.…”
Section: Bia In Patients Undergoing Peritoneal Dialysismentioning
confidence: 99%
“…Fluid overload is common among patients on peritoneal dialysis (PD), and it represents an important non-traditional risk factor of cardiovascular diseases in this group of patients [ 1 ]. Previous studies showed that clinically overt fluid overload is associated with decrease in patient and technique survival [ 2 , 3 ], excess peritonitis rate (with enteric organisms) [ 4 ], increase in left ventricular mass [ 5 ] and impaired quality of life [ 6 ]. However, assessment of volume status is frequently unreliable by traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid overload is more prevalent in PD patients than in HD patients [ 38 ]. In PD patients, ultrafiltration failure remains a major cause of treatment failure [ 39 ], and fluid overload is an independent predictor of mortality and negatively impacts life quality [ 40 , 41 ]. Increased vascular volume in the neck (i.e., rostral fluid shifts) may promote upper airway obstruction in OSA patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%